Effect of pretreated microstructure on the morphology and mechanical properties of low-carbon steel with IQ&P treatment - CHEN Lian-sheng; ZHANG Jian-yang; TIAN Ya-qiang; SONG Jin-ying; XU Yong; ZHANG Shi-hong (工程科学学报)
The effects of pretreated microstructure on the multiphase microstructure features at room temperature and the mechanical properties of low-carbon steel were studied by the treatment of water cooling after hot-rolling in the γ phase region or in the γ + α phase region followed by the treatment of intercritical reheating-quenching-partitioning (IQ&P). Two different pretreated microstructures, which are martensite and martensite + ferrite, are obtained by the two different hot-rolling and quenching processes. After IQ&P, the steel with martensite as pretreated microstructure, in which the volume fraction of retained austenite is 8. 2%, is turned into a multi-phase structure composed of lath intercritical ferrite, block tempered martensite, needle-like untempered martensite, and retained austenite. While the steel with martensite + ferrite as pretreated microstructure, in which the volume fraction of retained austenite is 14. 3%, is turned into a multi-phase structure composed of lath intercritical ferrite, block or needle-like untempered martensite, and short needle-like or block retained austenite. With the same IQ&P process parameters, the tensile strength of the steel with martensite as pretreated microstructure is 770 MPa, the elongation is 28%, and the product of strength and elongation is 21560 MPa·%. While the tensile strength of the steel with martensite + ferrite as pretreated microstructure is 834 MPa, the elongation increases to 36. 2%, and the product of strength and elongation reaches to 30190 MPa·%. In other words, the steel has obtained a good combination of strength and ductility.